1990
DOI: 10.1111/j.1600-065x.1990.tb00803.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐Cell Clones that react against Autologous Human Tumors

Abstract: T cells (derived from peripheral blood lymphocytes [PBL], lymph nodes or tumor tissues and restimulated with autologous tumor cells and expanded in interleukin-2 [IL-2]), when cloned, produce three functional classes of clone. Class I T-cell clones exhibit the phenotype of alpha/beta cytotoxic T lymphocytes (CD3+, CD8+, CD4-, WT31+), use their CD3-alpha/beta complexes for cognate function, and lyse the autologous tumor cells specifically in a major histocompatibility complex (MHC) Class I-restricted manner. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Amplified DNA was analyzed by nondenaturing agarose gel electrophoresis. 5 Al of the amplification reaction was electrophoresed on a 1.5% Tris-Borate-EDTA agarose gel (FMC Corp., Rockland, ME) in the presence of ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplified DNA was analyzed by nondenaturing agarose gel electrophoresis. 5 Al of the amplification reaction was electrophoresed on a 1.5% Tris-Borate-EDTA agarose gel (FMC Corp., Rockland, ME) in the presence of ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…The latter include reduction or loss of HLA class I antigen expression, which has been found to occur in -30% of surgically removed melanoma lesions (for review, see reference 1). Abnormalities in HLA class I antigen expression are likely to affect the biology of melanoma cells and their interactions with immune cells be-cause of the role of HLA class I antigens in cell proliferation (2)(3)(4), interaction of target cells with cytotoxic T cells (for review see reference 5), and susceptibility of malignant cells to natural killer (NK)' cell-mediated lysis (for review see reference 6). Besides contributing to the characterization of the machinery regulating HLA class I antigen synthesis and expression, analysis of the molecular mechanisms underlying reduction or loss of HLA class I antigen expression by melanoma cells provides the necessary background to correct these abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Many in vitro studies have shown the existence of specific immune interactions: cultured T cells derived either from PBL, lymph node, or the site of the tumor were found to display specific MHC-restricted regulatory or effector activities in response to autologous melanoma cells (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Encouraging results have been obtained with ex vivo expanded tumor-1.…”
Section: Introductionmentioning
confidence: 99%
“…The antitumor immune response is predominantly sustained by tumor-infiltrating T lymphocytes (TILs), consisting of CD4 ϩ and CD8 ϩ T cells (15). CD4 ϩ Th lymphocytes have been divided into Th1 and Th2 subpopulations, based on their functional properties and on the profile of secreted cytokines.…”
mentioning
confidence: 99%